CEH v11 : certified ethical hacker version 11 practice tests - Messier, Ric (Sybex/John Wiley & Sons, Inc., 2022)
Master CEH v11 and identify your weak spots CEH: Certified Ethical Hacker Version 11 Practice Tests are the ideal preparation for this high-stakes exam. Five complete, unique practice tests are designed to help you identify weak spots in your understanding, so you can direct your preparation efforts efficiently and gain the confidence--and skills--you need to pass. These tests cover all section sections of the exam blueprint, allowing you to test your knowledge of Background, Analysis/Assessment, Security, Tools/Systems/Programs, Procedures/Methodology, Regulation/Policy, and Ethics. Coverage aligns with CEH version 11, including material to test your knowledge of reconnaissance and scanning, cloud, tablet, and mobile and wireless security and attacks, the latest vulnerabilities, and the new emphasis on Internet of Things (IoT). The exams are designed to familiarize CEH candidates with the test format, allowing them to become more comfortable apply their knowledge and skills in a high-pressure test setting. The ideal companion for the Sybex CEH v11 Study Guide, this book is an invaluable tool for anyone aspiring to this highly-regarded certification. Offered by the International Council of Electronic Commerce Consultants, the Certified Ethical Hacker certification is unique in the penetration testing sphere, and requires preparation specific to the CEH exam more than general IT security knowledge. This book of practice tests help you steer your study where it needs to go by giving you a glimpse of exam day while there's still time to prepare. Practice all seven sections of the CEH v11 exam Test your knowledge of security, tools, procedures, and regulations Gauge your understanding of vulnerabilities and threats Master the material well in advance of exam day By getting inside the mind of an attacker, you gain a one-of-a-kind perspective that dramatically boosts your marketability and advancement potential. If you're ready to attempt this unique certification, the CEH: Certified Ethical Hacker Version 11 Practice Tests are the major preparation tool you should not be without.